4H-SiC double-layer thin n-base light triggered thyristor with a trenched-junction isolated amplifying gate. (October 2018) - Wang, Xi; Pu, Hongbin; Liu, Qing; An, Liqi
Abstract: In this paper, a new 4H-SiC double-layer thin n-base LTT with a trenched-junction isolated amplifying gate is proposed and investigated to compensate for the shortcomings of the conventional SiC amplifying gate structures. By using double-layer thin n-base structure, the turn-on performance of the pilot LTT is improved. According to simulations, the trenched-junction isolated amplifying gate works well and the turn-on delay of the proposed device is only 451 ns, when triggered by 500 mW/cm 2 ultraviolet light. Meanwhile, the breakdown voltage remains higher than 10 kV. Comparing with conventional resistance isolated amplifying gate and trench isolated amplifying gate, the proposed trenched-junction isolated gate structure shows better performances in both area utilization and blocking characteristic. Highlights: A SiC double layer thin n-base LTT with an amplifying gate (AG) is proposed and investigated for the first time. A new trenched-junction isolated AG structure is proposed to compensate for the shortcomings of conventional AG structures. The proposed device shows improved performances both in turn-on process and blocking state.